- #1

- 730

- 1

## Homework Statement

I'm just working through a textbook and there's a line in which I'm clearly missing something. What I want to do is show that from:

[tex] \bar{h^{TT}_{\mu \nu}} = A^{TT}_{\mu \nu} cos(\omega (t-z)) [\tex]

to

[tex] h^{TT}_{\mu \nu} = B^{TT}_{\mu \nu} cos(\omega (t-z)) [\tex]

## Homework Equations

[tex]\bar{h}_{\mu \nu} = h_{\mu \nu} - \frac{1}{2} \eta_{\mu \nu} h[\tex]

[tex]h = h^{\alpha}_{\alpha} = \eta^{\alpha \beta} h_{\alpha \beta}[\tex]

## The Attempt at a Solution

There's just one line where I have an issue, i think.

I've used the above equations to say:

[tex] \bar{h} = \eta^{\mu \nu}\bar{h}_{\mu \nu}[\tex]

then substituted the equation for [tex]\bar{h}_{\mu \nu}[\tex] to get:

[tex] \bar{h} = h - \frac{1}{2} \eta^{\mu \nu} \eta_{\mu \nu} h[\tex]

which is fine, but for it to work this last line must equal [tex]-h[\tex], I think and I'm not sure i see where that comes from.

thanks.

ftj